Peran Pembina dalam Pengelolaan Asrama Putri Kumang di Sekadau: Pendekatan Pendidikan Karakter - Musa Narang (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
This article discusses Asrama Putri Kumang located within the complex of SMK KelingKumang in Sekadau. This dormitory was established by the Yayasan Pendidikan KelingKumang as part of efforts to support the education and spiritual development of students. Thearticle examines the background of the dormitory's establishment, the role of spiritual leadersin its management, the fluctuation in the number of occupants over the years, as well as effortsto improve facilities and regulations within the dormitory. The impact of technology andchallenges faced in managing dormitory residents are also addressed. The article underscoresthe importance of the role of spiritual leaders in shaping the character and outlook of students'lives, and encourages parents to entrust their children to the management of the dormitory bysisters.